2021
DOI: 10.1111/ejss.13206
|View full text |Cite
|
Sign up to set email alerts
|

Do tree species affect decadal changes in soil organic carbon and total nitrogen stocks in Danish common garden experiments?

Abstract: Temperate forest soils are often considered as an important sink for atmospheric carbon (C), thereby buffering anthropogenic CO 2 emissions. However, the effect of tree species composition on the magnitude of this sink is unclear.We resampled a tree species common garden experiment (six sites) a decade after initial sampling to evaluate whether forest floor (FF) and topsoil organic carbon (C org ) and total nitrogen (N t ) stocks changed in dependence of tree species (Norway spruce-Picea abies L., European bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Approximately 60% of the studies that compared topsoil OC stocks under several tree species observed tree species effects on topsoil OC stocks, while the other 40% did not (Boca et al, 2014;Langenbruch et al, 2012;Mayer et al, 2020;Peng et al, 2020;Vesterdal et al, 2013). The ranking of tree species with increasing topsoil OC and N stocks tended to be opposite to the ranking for the forest floor (Fleck et al, 2019;Peng et al, 2020;Rodeghiero et al, 2018;Steffens et al, 2022;Vesterdal et al, 2013).…”
Section: Changes In Soil Oc Are Driven By Inputs From Vegetation Vers...mentioning
confidence: 94%
See 3 more Smart Citations
“…Approximately 60% of the studies that compared topsoil OC stocks under several tree species observed tree species effects on topsoil OC stocks, while the other 40% did not (Boca et al, 2014;Langenbruch et al, 2012;Mayer et al, 2020;Peng et al, 2020;Vesterdal et al, 2013). The ranking of tree species with increasing topsoil OC and N stocks tended to be opposite to the ranking for the forest floor (Fleck et al, 2019;Peng et al, 2020;Rodeghiero et al, 2018;Steffens et al, 2022;Vesterdal et al, 2013).…”
Section: Changes In Soil Oc Are Driven By Inputs From Vegetation Vers...mentioning
confidence: 94%
“…How to cite this article: Steffens, C., Beer, C., Schelfhout, S., & Vesterdal, L. (2022). Tree species affect the vertical distribution of soil organic carbon and total nitrogen.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Grassland areas, for instance, may demonstrate lower SOC levels due to vegetation disturbance and intensive grassland management (e.g., the regular application of lime and fertilizers, tillage, grazing etc). In contrast, forestry sites might show variations in SOC and soil pH influenced by tree species, root systems, and potential acidification from organic matter decomposition (Steffens et al, 2022;Wang et al, 2013). Industrial cutaway areas are expected to display distinct SOC and soil pH profiles owing to alterations in peatland structure and potential environmental impact.…”
Section: Introductionmentioning
confidence: 99%